Quantitative Analysis of Synaptic Ultrastructure in The Mouse Cerebellum by Focused Ion Beam-Scanning Electron Microscopy: A novel Method for Structural Analysis - Elhanbaly, Ruwaida; Fukazawa, Yugo (Journal of Advanced Veterinary Research, 2022)
The present study was carried out to investigate the synaptic ultrastructure of the mouse cerebellum using focused ion beam scanning electron microscopy (FIB-SEM). The experiment were performed using seven weeks old wild type mice. In the present work, we used a newly established morphological investigation method of axospinous synapses (FIB-SEM). This method enables fully automated acquisition of serial ultrastructural data at a spatial resolution of 10 nm in z-axis without the ultrastructure distortions. FIB-SEM enabled easily identification of axospinous synapses in the mouse cerebellum where individual synaptic ultra-structure can be easily identified and measured. The results indicated that, the cerbellum axospinous synapses have presynaptic and postsynaptic compartment. The presynaptic compartment consists of the presynaptic axonal varicosity, synaptic vesicles and mitochondria. The postsynaptic compartment consists of the dendritic spine, postsynaptic density and smooth endoplasmic reticulum and spine apparatus. The volume of presynaptic and postsynaptic compartments was varaible. The results indicated a significant positive correlation between presynaptic compartments as well as between postsynaptic compartments. Moreover, this study represented novel correlations between presynaptic and postsynaptic parameters. Â